Acceleration Return to Work Process After Accidents in the Manufacturing Industry – Literature Review - Sadat, Lubna; Hidayah, Nurul; Iskandar, Dede (UI Scholars Hub, 2024)
The manufacturing industry typically requires capacities on a large scale, increasing the risk of workplace accidents and illnesses. Thus, a stringent Occupational Health and Safety (OHS) guideline is needed, notably through early Return to Work (RTW) policies. In this review we explore how the acceleration of the RTW process influences employees, factories, and policy after accidents. Using a literature review approach, this research collected the data and information from from books, journals, and articles discussing the topic of OHS management in domestic and overseas factories.Acceleration of RTW included gradual task modifications, alternative tasks, and workstation adjustments to facilitate workers’ return post-injury. RTW positively impacted workers by fostering a sense of value, maintaining income, preserving physical well-being, sustaining a positive work image, and reducing emotional stress. Job modifications within the